Aflasafe, a nature based bioprotectant to mitigate aflatoxin contamination in Africa. - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2023)
Aflatoxin is a fungal toxin that contaminates crops in Africa and to address this, IITA and partners have developed aflasafe to reduce crop contamination by 100% for safety